Marketing and advertising in the age of artificial intelligence and its impact on the consumer experience - Solórzano Martínez, Diana Paola; Ochoa Herrera, Verónica Alexandra; Yánez Cabrera , Jenny Susana (Scripta Mundi, 2025)
The objective of this study is to research the effects of artificial intelligence (AI) on marketing and advertising strategies, with a focus on how these technologies influence the consumer experience. Through a qualitative and quantitative analysis approach, the most common applications of artificial intelligence in marketing, including personalization of content and chatbots, are examined, highlighting both their benefits and the associated ethical and practical challenges. The findings suggest that AI has the potential to significantly improve consumer satisfaction by delivering more personalized and relevant experiences; however, concerns about data privacy and distrust of automated technologies are also identified. The study acknowledges certain limitations, such as possible biases in sample selection, difficulties in measuring complex concepts such as consumer perception, and the rapid technological obsolescence inherent in the subject. These limitations underscore the need for future research that continues to integrate mixed approaches and consider the dynamic context of technology and consumer behavior. The research provides an updated view on the transformative role of AI in marketing, while identifying key areas for the ethical and effective development of these technologies for the benefit of both businesses and consumers.
Keywords: advertising; artificial intelligence; consumers; marketing